2012
DOI: 10.1143/apex.5.036501
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam-Induced Decomposition Mechanisms of High-Sensitivity Chlorinated Resist ZEP520A

Abstract: ZEP520A (1:1 copolymer of α-chloromethacrylate and α-methylstyrene, ZEON) is a main-chain scission-type positive-tone resist used for electron beam (EB) lithography and is known for its high sensitivity and high resolution. In this study, ZEP520A was irradiated using a 100 kV EB, and the decomposition mechanisms were analyzed by gel permeation chromatography, Fourier transform IR spectroscopy, NMR spectroscopy, and pulse radiolysis. Chlorines were confirmed to easily dissociate as Cl- ions (dissociative electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The increase of roughness at the positive tone region of ZEP resist may have connected to the decomposition of ZEP resists. The decomposition mechanism of ZEP resists under EB irradiations has been reported [11,15]. The dissociation of chlorine from the main chain was confirmed and ZEP resists underwent β-scission to form terminal double bonds (C=CH 2 ) at both alpha-chloro-methacrylate group and alpha-methyl-styrene group [11].…”
Section: 5mentioning
confidence: 89%
See 2 more Smart Citations
“…The increase of roughness at the positive tone region of ZEP resist may have connected to the decomposition of ZEP resists. The decomposition mechanism of ZEP resists under EB irradiations has been reported [11,15]. The dissociation of chlorine from the main chain was confirmed and ZEP resists underwent β-scission to form terminal double bonds (C=CH 2 ) at both alpha-chloro-methacrylate group and alpha-methyl-styrene group [11].…”
Section: 5mentioning
confidence: 89%
“…The decomposition mechanism of ZEP resists under EB irradiations has been reported [11,15]. The dissociation of chlorine from the main chain was confirmed and ZEP resists underwent β-scission to form terminal double bonds (C=CH 2 ) at both alpha-chloro-methacrylate group and alpha-methyl-styrene group [11]. The decomposition of the main-chain into smaller parts may have caused the increase of its surface roughness.…”
Section: 5mentioning
confidence: 92%
See 1 more Smart Citation
“…In previous work, the mechanisms of degradation of ZEP520A were investigated based on analysis of the final products of degradation by means of X-ray photoelectron spectroscopy (XPS), gel permeation chromatography (GPC), Fourier transform IR spectroscopy (FT-IR), and nuclear magnetic resonance (NMR) spectroscopy. Efficient random chain scission with a G-value of approximately 8 was observed by means of GPC [7], and the decomposition of C−Cl bonds in irradiated ZEP520A was observed using XPS and FT-IR [6,7]. Moreover, NMR spectroscopy confirmed that terminal double bonds (−CH=CH 2 ) generated via main-chain scission were formed at both the α-chloromethacrylate unit and α-methylstyrene unit [7].…”
Section: Introductionmentioning
confidence: 92%
“…It is known that its halogen groups are easier to react to the electron or EUV light, so it is cut inside molecular and promoted to dissociate combinations. In addition, gL3002-T has simple chemical structure which is same formula of ZEP520-A [4] as shown in Fig. 1.…”
Section: Experiments Samplementioning
confidence: 99%